2007
DOI: 10.2337/dc06-1854
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones and Risk of Repeat Target Vessel Revascularization Following Percutaneous Coronary Intervention

Abstract: OBJECTIVE -Thiazolidinediones (TZDs) (rosiglitazone and pioglitazone) are a class of antidiabetes agents that have a high affinity for peroxisome proliferator-activated receptor-␥. TZDs initiate a multitude of physiologic processes that may elicit benefits as systemic agents for the prevention of restenosis requiring revascularization following percutaneous coronary intervention (PCI). Numerous trials have evaluated the impact of TZDs on repeat target vessel revascularization (TVR) in patients following PCI; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…TZDs decrease vascular smooth muscle cell and neointimal proliferation. A meta-analysis of seven clinical trials including 608 individuals has shown a reduction in the rate of restenosis with TZD treatment (7). Furthermore, recent evidence suggests reduction in carotid intima-medial thickness (IMT) with TZDs (8 -11).…”
Section: On 21 May 2007 An Article Appeared On the New England Journmentioning
confidence: 99%
“…TZDs decrease vascular smooth muscle cell and neointimal proliferation. A meta-analysis of seven clinical trials including 608 individuals has shown a reduction in the rate of restenosis with TZD treatment (7). Furthermore, recent evidence suggests reduction in carotid intima-medial thickness (IMT) with TZDs (8 -11).…”
Section: On 21 May 2007 An Article Appeared On the New England Journmentioning
confidence: 99%
“…Several small, randomized trials have been performed in diabetic and nondiabetic patients after bare metal stent implantation, with clinical and angiographic endpoints. Metaanalyses of these trials suggest that TZDs may reduce late lumen loss and need for further target vessel revascularization, with more convincing effects in diabetics and with pioglitazone than in nondiabetics or with rosiglitazone (119)(120)(121). It has also been hypothesized that salutary endothelial effects of PPAR-␥ activation might reduce the risk of stent thrombosis after drugeluting stent implantation ( 122 ), but to date there are no data to either corroborate or refute this.…”
Section: Endothelial Function Vascular Smooth Muscle Cell Proliferatmentioning
confidence: 96%
“…Pioglitazone administration to insulin‐resistant non‐diabetic patients after stroke was just reported to be associated with a reduction in stroke and in myocardial infarction in the Insulin Resistance Intervention after Stroke (IRIS) trial, as further discussed in the accompanying Commentary by Professor Inzucchi, recalling the findings of the PROspective pioglitAzone Clinical Trial In macroVascular Events (PROACTIVE) study among diabetic patients . Looking at another important manifestation of coronary atherosclerosis, a meta‐analysis of seven randomized controlled trials involving 608 people following percutaneous coronary intervention showed that the use of either rosiglitazone or pioglitazone was associated with a more than 50 % reduction in the need for repeat target vessel revascularization; presaging the IRIS findings, this risk was similarly reduced among individuals with and without diabetes . Can it be that the use of treatment strategies associated with improvement in glycemia, but not intrinsically increasing the likelihood of hypoglycemia, are indeed the right approaches?…”
mentioning
confidence: 87%